Hands-On Nuxt. js Web Development : Build Universal and Static-Generated Vue. js Applications Using Nuxt. js. - Kok, Lau Tiam (Packt Publishing, 2020)
Nuxt.js is a progressive web framework for adding SSR capabilities to Vue.js apps. This practical guide will help you up and running with the fundamentals of Nuxt.js, how to integrate it with the latest version of Vue.js and enable you to build an entire project including authentication, testing, and deployment with Nuxt.js and Vue.js.